Synthesis, Stability, and Biological Evaluation of Novel Aminoderivatives Incorporating the Aza-Acridine Scaffold - Maria Karelou; Anthi Panara; Eleftheria Chatziorfanou; Aikaterini F. Giannopoulou; Dimitrios J. Stravopodis; Evagelos Gikas; Ioannis K. Kostakis (Molecules)
Several new amino-substituted aza-acridine derivatives bearing one or two basic side chains have been designed and synthesized. Their anticancer activities were evaluated in vitro against two human cancer cell lines: T24 (urothelial bladder carcinoma, malignancy grade III) and WM266-4 (metastatic melanoma). Some of the synthesized compounds induced significant antiproliferative effects, with WM266-4 cells appearing more susceptible than T24 cells. This apparent cell-type selectivity may reflect differences in the mutational profiles and molecular target landscapes between the two cancer models. A stability study under hydrolytic conditions, based on a validated method, indicated that the most active compounds were stable under aqueous conditions. Computational analysis further supported the stability of these analogs, providing insights into the structure–stability relationships of the synthesized compounds.